Career readiness and well-being: The mediation role of strategies for coping with career indecision. (April 2023) - Russo, Angela; Zammitti, Andrea; Zarbo, Rita
In the uncertain and flexible labour market, some people experience indecision in dealing with career choices, despite having career readiness. The present research explored the relationship between career readiness, strategies for coping with career indecision, and well-being. Participants were 529 people aged between 18 and 60 ( M  = 26.57; SD  = 6.83). The survey included: Readiness scale of the Career Transition Inventory, Productive scale and Support Seeking scale of Strategies for coping with career indecision, Flourishing Scale and Satisfaction with life scale. Results show that both productive and support-seeking strategies mediate the association between career readiness and flourishing and between career readiness and life satisfaction. As implications for career guidance, in addition to favouring career readiness, counsellors could promote productive strategies for coping with career indecision– and in some cases, support-seeking strategies–, to help people transform the experience of career indecision from insurmountable obstacles into an opportunity to act towards well-being.